STUDI EKSPERIMENTAL PEMBUATAN KAMPAS REM BERBAHAN SERAT SABUT TERHADAP PENGUJIAN KEAUSAN - Anugrah Putra Juang Zebua; Dhimas Wicaksono; Sehono Sehono (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2022)
Brake pads are media or components on the brakes that work to slow down or stop the vehicle. In general , brake dregs that are widely marketed are made of asbestos, semi-metal and non - asbestos materials . Asbestos-based brake pads are known to be environmentally unfriendly and carcinogenic. Therefore, the manufacture of non-asbestos-based brake pads with coconut fiber as the base material needs to be developed. This study aims to make brake linings made from coconut fiber, epoxy resin, and coconut charcoal. The manufacture of brake linings is made in 2 variations of fiber direction, namely horizontal and irregular as well as variations in the weight of the material with each consisting of 3 specimens. The brake lining specimens that have been made are tested for specific wear rates using the ogoshi method. The results of the wear test of brake linings made from coconut fiber with horizontal variations have an average wear value of 3,37 kg and irregular brake lining variations get a wear value of 3,83 kg . The specific wear value of a brake lining is influenced by the direction of the fiber and the composition of the fiber weight, the weight of the charcoal, and the weight of the epoxy resin. Based on data on horizontal and irregular brake pads, the more fiber and coconut charcoal it will affect the wear value.